Contribuições da investigação em sala de aula para uma aprendizagem das secções cônicas com significado - Macena, Marta Maria Maurício (2007)
In this work, the didactical possibilities of investigation use in classroom, through an experience with high school students from Federal Center of Technological Education of Paraíba, as well as the study of conic sections were analysed. In order to fulfill our goals the theoretical conceptions concerning the meaninful learning in conection with the investigation of mathematics history were taken into account. The classroom research occurred by means of activities which encouraged the learner to investigate his own concepts on the conic sections. The results of the proposed activities showed the effectiveness and the efficiency of such a methodology as regards the making up of the required knowledge. They also reveal that the investigation in the classroom guides the ones involved, in this process, to have a wider look at the origins, the methods used and the several representations presented by mathematics that certainly lead, specially the students, to a meaninful learning